2017
DOI: 10.1016/j.ijdevneu.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Cellular protein and mRNA expression of β1 nicotinic acetylcholine receptor (nAChR) subunit in brain, skeletal muscle and placenta

Abstract: The β1 nicotinic acetylcholine receptor (nAChR) subunit is a muscle type subunit of this family and as such, is found predominantly in muscle. Recent reports document its expression in other tissues and cell lines including adrenal glands, carcinomas, lung and brain. However, the majority of studies were of tissue lysates, thus the cellular distribution was not determined. This study aimed to determine the cellular distribution of the β1 nAChR subunit in the brain, at both the mRNA and protein levels, using no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Other chemicals within cigarettes may also act though upon the placenta. The placenta expresses nicotinic acetylcholine receptor (nAChR) subunits that regulate TB cell invasion but whose expression and signaling pathway can be usurped by nicotine contained within tobacco smoke (Lips et al, 2005;Machaalani et al, 2014Machaalani et al, , 2018Aishah et al, 2017;Chen et al, 2020). For instance, nicotine acting through nAChR induced endoplasmic reticulum stress in rat pTGC (Wong et al, 2016).…”
Section: Smokingmentioning
confidence: 99%
“…Other chemicals within cigarettes may also act though upon the placenta. The placenta expresses nicotinic acetylcholine receptor (nAChR) subunits that regulate TB cell invasion but whose expression and signaling pathway can be usurped by nicotine contained within tobacco smoke (Lips et al, 2005;Machaalani et al, 2014Machaalani et al, , 2018Aishah et al, 2017;Chen et al, 2020). For instance, nicotine acting through nAChR induced endoplasmic reticulum stress in rat pTGC (Wong et al, 2016).…”
Section: Smokingmentioning
confidence: 99%
“…Once maternal placental circulation begins toward the end of the first trimester (week 8–12), the uterine vessels are maximally dilated. The uterine arteries have an extensive sympathetic nerve supply and express additional receptors such as 5HT2, arginine vasopressin receptors 1A, and nicotinic acetylcholinergic receptors which when activated could bring about uterine artery vasoconstriction (Koukoulas et al, ; Ugun‐Klusek et al, ; Aishah et al, ). The effect is largely observed in the postorganogenic period.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we consider that IGFBP4 is a strong candidate gene for CN. CHRNB1 is involved in muscle contraction and muscle fibre development [ 74 ] and is specifically and highly expressed in muscle. The human PheWAS results showed that CHRNB1 was significantly associated with skeletal traits.…”
Section: Discussionmentioning
confidence: 99%